Early diagnosis of acute coronary syndrome - Katus, Hugo; Giannitsis, Evangelos; Brückmann, Martina; Friedrich, Matthias (European heart journal, 2017)
The diagnostic evaluation of acute chest pain has been augmented in recent years by advances in the sensitivity and precision of cardiac troponin assays, new biomarkers, improvements in imaging modalities, and release of new clinical decision algorithms. This progress has enabled physicians to diagnose or rule-out acute myocardial infarction earlier after the initial patient presentation, usually in emergency department settings, which may facilitate prompt initiation of evidence-based treatments, investigation of alternative diagnoses for chest pain, or discharge, and permit better utilization of healthcare resources. A non-trivial proportion of patients fall in an indeterminate category according to rule-out algorithms, and minimal evidence-based guidance exists for the optimal evaluation, monitoring, and treatment of these patients. The Cardiovascular Round Table of the ESC proposes approaches for the optimal application of early strategies in clinical practice to improve patient care following the review of recent advances in the early diagnosis of acute coronary syndrome. The following specific 'indeterminate' patient categories were considered: (i) patients with symptoms and high-sensitivity cardiac troponin <99th percentile; (ii) patients with symptoms and high-sensitivity troponin <99th percentile but above the limit of detection; (iii) patients with symptoms and high-sensitivity troponin >99th percentile but without dynamic change; and (iv) patients with symptoms and high-sensitivity troponin >99th percentile and dynamic change but without coronary plaque rupture/erosion/dissection. Definitive evidence is currently lacking to manage these patients whose early diagnosis is 'indeterminate' and these areas of uncertainty should be assigned a high priority for research.